ESR STUDY OF THE COMPLEX-FORMATION BETWEEN CU(CLO4)2 AND A FUNCTIONALIZED SILICA-GEL SURFACE - Dias, N. L.; Gushikem, Y.; Moreira, J. C.; Polito, W. L.; Rodrigues, E. (Soc Brasileira Quimica, 1994)
The formation of the complex between Cu(ClO4)2 and a silica gel surface grafted with benzimidazole groups has been investigated by ESR. The parameters of the ESR spectrum of the complex obtained are presented and used to determine the most probable immediate environment of the complex formed on the surface of the solid phase. The fit of the theoretical expressions with the experimental data is very reasonable.
Keywords: BENZIMIDAZOLE; FUNCTIONALIZATION OF SILICA GEL